Feedback and incentives: experimental evidence - Tor Eriksson; Anders Poulsen; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2008)
This paper experimentally investigates the impact of different pay and relative performance information policies on employee effort. We explore three information policies: No feedback about relative performance, feedback given halfway through the production period, and continuously updated feedback. The pay schemes are a piece rate payment scheme and a winner-takes-all tournament. We find that, regardless of the pay scheme used, feedback does not improve performance. There are no significant peer effects in the piece-rate pay scheme. In contrast, in the tournament scheme we find some evidence of positive peer effects since the underdogs almost never quit the competition even when lagging significantly behind, and frontrunners do not slack off. Moreover, in both pay schemes information feedback reduces the quality of the low performers' work.
urn:nbn:de:101:1-2008041447
Keywords: C70; 330; Performance pay; tournament; piece rate; peer effects; information; feedback; evaluation; experiment; Leistungsmotivation; Leistungsorientierte Vergütung; Personalbeurteilung; Information; Extensives Spiel; Test; Theorie